Air Safety Investigation - Schuurman, Michiel (TU Delft OPEN Publishing, 2025)
"Air Safety Investigation – The Journey" is an introductory book that explores the world of air safety investigation. Unlike a how-to manual for investigating aviation accidents, this book focuses on the essential knowledge and mindset required to conduct a safety investigation. It covers the various phases of an investigation, from gathering facts to formulating safety recommendations, with each chapter addressing a different relevant aspect. With the increasing complexity of investigations, critical thinking, logic, and speculation are essential skills for investigators to possess. This book delves into these topics, offering thought-provoking examples and questions to address the challenges of drawing conclusions and obtaining positive investigative outcomes. Its aim is to help students and readers interested in air safety develop the necessary mindset and knowledge to conduct an investigation. By the end of the book, readers will gain a deeper understanding of the complexities involved in an air safety investigation.